HYPERTROPHIC CARDIOMYOPATHY WITH PARTIAL ANOMALOUS PULMONARY VENOUS CONNECTION AND ATRIAL SEPTAL DEFECT: A RARE PRESENTATION - M, Alphonsa; R, Karthik; Gowda, Satish C; Patil, Navin; O, Balaji; Kotian, Rahul (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Hypertrophic cardiomyopathy (HOCM) is characterized by heterogeneous clinical expression, unique pathophysiology, and diverse natural history. Coexistence of arterial septal defect and partial anomalous pulmonary venous connection (PAPVC) is very rare. Since HOCM is a congenital defect, coexistence of other congenital defects should be kept in mind when we treat the patients. Only very few cases of HOCM with coexisting congenital anomalies have been reported so far in medical literature. Hence, we report a case of HOCM with atrial septal defect and PAPVC in a 49-year-old male patient.